Platformer Game Contents Creative System using Paper and Its Effects - 백재순; 이진우; 오규환 (한국컴퓨터게임학회논문지, 2019)
We have developed a system that allows users to play the contents of a flat former game drawn on an A4 size paper on a mobile device. If game contents drawn in a paper drawing are recognized through a camera of the mobile device, the game contents can be converted into digital and enjoyed in a mobile application. The user directly draws a game object using a writing instrument in a paper drawing. In order to enhance the object design convenience, the core game object is patterned and a new combination pattern can be created by combining meaningful patterns. In addition, to complement the limited size of the map that can be drawn on one piece of paper, we added the ability to construct a stage by combining the maps. Game components other than the object of the game drawn in the paper drawing can be added inside the system, thereby providing a highly flexible content creation. In order to supplement the process of repetitively creating game contents through paper drawings and converting them to digital, we made it possible to create and modify game contents in the system. The service model proposed in this study is to provide the experience of digital game contents creation in conjunction with unplugged activities for children. In this way, it will be possible to motivate creative activities by linking traditional unplugged activities for children with digital activities, and cultivate software literacy that fits the digital age.
Keywords: Game Map Design; Level Design; Pattern Recognition; Platformer Game; Game Making